(untitled) (International Journal of Food and Nutritional Sciences, 2022)
One of the advancements brought forth by the industrial age is 3D printing technology. It has been a part of our life for a long time. It is quickly evolving and employed in a variety of industries, including the aviation and defense sectors. In recent years, the medical industry has frequently favored this miraculous production technique. This paper introduces 3D printer technology, discusses various 3D printing techniques, and refers to the usage of this technology in biomedical applications. The present work reviews the use of 3D Printing technology in the major areas of medical fields like prosthetics, medical devices, implants, novel drug delivery systems, and personalized drugs. The findings of this review revealed that 3D printing has received a lot of attention in the medical field in recent years due to several characteristic features like flexibility, ease of production, and finally the cost-effectiveness of the technology. However, there are still safety and efficacy concerns about the same which need to be resolved in the future.